Preparation, characterisation and applications : Boron nitride nanotubes (BNNTs), BNNTs-graphene hybrid and their polymer nanocomposites - Kakarla, Akesh Babu (2018)
Boron nitride nanotubes (BNNTs) are unique one-dimensional crystal structures exfoliated from boron nitride (BN). In recent years, BNNTs have drawn attention because of their exceptional properties. The physicochemical properties including thermal and electrical insulation, high repulsion to water molecules, acid resistance, high hydrogen storage capacity and mechanically robust as graphene. There are various methods for the preparation of BNNTs such as top-down, bottom-up, chemical vapour deposition and co-precipitation process. Among that, large-scale production of BNNTs by using co-precipitation method is a promising way for industrialisation. In this work, the synthesis of BNNTswasachieved by co-precipitation and annealing route using amorphous boron, ferric nitrate nanohydrate (Fe(NO3)3.9H2O and urea (CO(NH2)2) as the raw materials. The BNNTs were later combined with graphene to produce novel hybrid structure through liquid-phase exfoliation method. Graphene was produced through Hummer’s method followed by reduction and purification process. Two types of polymer nanocomposites were prepared by using solvent mixing method. (a) BNNTs incorporated with polycaprolactone (PCL) to investigate the mechanical and thermal properties and (b) Graphene reinforced with polylactic acid (PLA) to study the toxicity of the nanocomposite.The polymer nanocomposite of BNNT reinforced with PCL were characterizedby using scanning electron microscope (SEM), thermal gravimetric analysis (TGA), X-ray diffraction (XRD), UV-visible spectrometer and tensile test. The tensile strength was increased by 101 % for PCL incoprated with 5 wt% of BNNTs compared to the pure PCL. However, in thermal analysis PCL-2BNNTs and PCL-5BNNTs showed thesame decomposition compared to pure PCL. There were 1 % to 4 % residues of PCL-2BNNTs and PCL-5BNNTs due to thepresence of BNNTs. The biocompatibility of PLA-graphene was tested by using Caenorhabditiselegans (C. elegans). The PLA-graphene did not show any negative effects andoutcomehas no cause of toxicity on the human organism. As a result, it was determined that the polymer nanocomposites are applicable in mechanical and biomedical applications.